Fast-cycle hydrogen peroxide nebulization against frequent healthcare-associated micro-organisms: efficacy assessment. (July 2021) - Cobrado, L.; Ramalho, P.; Ricardo, E.; Azevedo, M.-M.; Rodrigues, A.G.
Summary: Background: Hydrogen peroxide (H2 O2 )-based technology is currently used with the aim of controlling microbial contamination in hospital settings. However, the long cycles required result in prolonged room turnover time, thus precluding a wider implementation of the technology. Aim: To assess the efficacy of a shorter cycle of nebulized H2 O2 against healthcare-associated micro-organisms, further comparing among multidrug-resistant and multidrug-susceptible strains. Methods: The efficacy of a standard cycle (1 h) and of a faster cycle (15 min) of a 7% H2 O2 nebulized solution was compared against bacteria and yeasts. MDR and MDS strains were inoculated on polyvinyl chloride, stainless steel, linoleum, napa leather, and formica coupons, and their growth ability was compared. Findings: Globally, the mean efficacy of the standard cycle ranged between 82.5% (±17.0) and 95.9% (±8.3), while the efficacy of the fast cycle ranged between 84.4% (±17.0) and 95.7% (±10.5). No statistically significant differences were found for the majority of the tested cycles and materials. For all the tested strains, no differences were found regarding the efficacy of cycles. Conclusion: The very high disinfection efficacy of the fast cycle was found to be similar to that of the standard cycle. Moreover, a similar efficacy was also demonstrated when comparing between multidrug-resistant and multidrug-susceptible strains. This study supports a wider implementation of the technology, with the expected advantages of reducing room turnover time, costs, and indirect infection transmission. Further assessment of the efficacy of this faster cycle against other emergent microbial global threats would be highly recommended.